Blistering eruptions following isotretinoin therapy for hidradenitis suppurativa: a case report - Anaba, Ehiaghe L.; Oaku, Ruth I. (International Journal of Research in Medical Sciences, 2019)
A 33-year-old male was treated with isotretinoin (20mg daily) for hidradenitis suppurativa. After 6 weeks on the medication, he developed symmetrical erythematous tense blisters on the lower legs. Report of biopsy done was of intraepidermal blisters with superficial dermal lymphohistiocytic infitrates. He was commenced on oral prednisolone 30mg daily and Isotretinoin was withdrawn. The blisters resolved over a 2week period. The lesions of hidradenitis suppurativa were noticed to have improved with the short course of isotretionoin.